Isolation and identification of fungi found in contaminated fermented milk and antifungal activity of vanillin - Xu Pei; Mekonen Tekliye; Mingsheng Dong (Food Science and Human Wellness)
Fungi contamination is an important factor affecting the quality and commercial value of fermented milk. Vanillin is known as a safe and efficient natural antimicrobial additive with great potential value as a food bio-preservative. In this study, the microbiological quality of fermented milk of different brands retailed in China and the antimicrobial activity of vanillin were investigated. A total of 27 fermented milk samples were purchased and evaluated. Fungal isolates obtained were characterized by DNA sequencing of the internal transcribed spacer (ITS) region. The effects of vanillin on the growth of fungi were studied by plate dilution method, radical colony diameter, and mycelium biomass. The result showed that 14.8% of the samples were contaminated with three different species of fungi with Cladosporium spp. being the most predominant fungal contaminant. The study further showed that vanillin had significant inhibitory activity against the growth of the fungi species. The cell number, radical colony diameter, and the mycelium biomass of the fungal contaminant were significantly reduced by the inhibitory action of the vanillin. The study thus provides reliable data evidence that will help relevant stakeholders in the fermented milk industries to improve their quality control strategies and consider vanillin as a bio-preservative with the potential to increase the shelf-life and safety of fermented milk.